2018
DOI: 10.1111/ppl.12737
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous melatonin enhances salt stress tolerance in maize seedlings by improving antioxidant and photosynthetic capacity

Abstract: Melatonin (N-acetyl-5-methoxytryptamine) is an important biological hormone in many abiotic stress responses and developmental processes. In this study, the protective roles of melatonin were investigated by measuring the antioxidant defense system and photosynthetic characteristics in maize under salt stress. The results indicated that NaCl treatment led to the decrease in plant growth, chlorophyll contents and photochemical activity of photosystem II (PSII). However, the levels of reactive oxygen species inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
119
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(145 citation statements)
references
References 76 publications
24
119
2
Order By: Relevance
“…Similarly, Sumaira et al (2017) suggested the inducing role of melatonin in the biosynthesis of various phytochemicals [54]. Herein, similar observations were documented, which involve augmentation in the synthesis of phenolic compounds in calli exposed to melatonin [29,42,43,45]. A similar trend was observed for UV-C treatments.…”
Section: Quantification Of Phenylpropanoid Metabolites Via Hplcsupporting
confidence: 77%
See 1 more Smart Citation
“…Similarly, Sumaira et al (2017) suggested the inducing role of melatonin in the biosynthesis of various phytochemicals [54]. Herein, similar observations were documented, which involve augmentation in the synthesis of phenolic compounds in calli exposed to melatonin [29,42,43,45]. A similar trend was observed for UV-C treatments.…”
Section: Quantification Of Phenylpropanoid Metabolites Via Hplcsupporting
confidence: 77%
“…However, the mechanism of action is not clearly elucidated yet, but research has shown that UV stress is encountered in plants by modulating key enzymes productions, such as CHS (chalcone synthase), PAL (phenylalanine ammonia-lyase) and through the rapid accumulation of phenolic compounds [39][40][41]. Exogenous applications of melatonin affect plants' physiological processes [42,43]. The effects of different melatonin concentrations on purple basil callus cultures were also studied for flavonoids and phenolics production.…”
Section: Influence Uv-c Radiations and Melatonin On Total Phenolic Anmentioning
confidence: 99%
“…However, the main function of melatonin on enzymatic or non-enzymatic system-mediated ROS scavenging in alfalfa plants still requires further study. The positive effects of melatonin on antioxidant enzymes system under salt stress conditions is also confirmed in tomato seedlings and maize seedlings [57,58]. Exogenous application of melatonin promotes plant growth and stress resistance mainly through enhancing the plant endogenous melatonin level.…”
Section: Discussionmentioning
confidence: 69%
“…Salt is one of the main factors affecting ecological environments and inhibiting crop growth. With the expansion of saline-alkali land areas in China, crop yields and quality have decreased gradually [34]. The salt stress damage to plants is mainly manifested through osmotic stress, ion stress, and antioxidant system and hormone signal transduction, among other phenomena [35,7].…”
Section: Discussionmentioning
confidence: 99%
“…Castanares et al [36] concluded that salt stress leads to K + / Na + imbalance, destroys cell membrane integrity, and reduces potassium retention, while exogenous melatonin effectively relieved this effect, which might be related to the activity of related enzymes in cells. Similarly, melatonin could significantly reduce Na + accumulation and increase K + content in maize seeds under salt stress [34]. Yu et al [51] proposed a novel mechanism for melatonin-mediated salt tolerance, i.e., melatonin supplementation decreased the oxidative damage induced by salinity, perhaps by directly scavenging H 2 O 2 or enhancing the activities of antioxidative enzymes.…”
Section: Discussionmentioning
confidence: 99%